Highly oxidized semiconducting coordination polymers: coupled oxidation and coordination of guanidine electron donors - Trumm, Christine Helga; Stang, Simone; Eberle, Benjamin; Kaifer, Elisabeth; Meyerbröker, Nikolaus; Zharnikov, Michael; Hübner, Olaf; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2012)
Redox and coordination processes are coupled in the course of reactions of the organic electron donors 1,2,4,5-tetrakis(tetramethylguanidino)benzene (1) and 1,2,4,5-tetrakis(N,N′-dimethyl-N,N′-ethyleneguanidino)benzene (2) with silver salts. Experiments with several different silver salts show that the product structure is significantly affected by the properties of the anion in these salts. Chain polymers are the products of reactions with AgPF6 or AgBF4, in which dicationic organic building blocks are connected by silver ions. Experiments with AgNO3 yielded either dinuclear complexes (with 1) or 2D networks (with 2). If the salt Ag[AlOC(CF3)34], featuring a weakly coordinating anion, was used, simple silver-free salts of the guanidine dication were obtained. The thermal stability, optical properties, and electrical conductivity were studied in detail for the product polymer [(1)Ag](PF6)3n. From the temperature dependence of the electric conductivity, this compound was found to be a semiconductor with a band gap of approximately 3 eV. The experiments were complemented by quantum chemical calculations at density-functional-theory level on the band structure of this and a related polymer. The electronic situation was further analyzed with the aid of molecular model complexes, which were either synthesized or calculated.